PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA KOKAMI TERHADAP PRESTASI BELAJAR PADA MATERI TERMOKIMIA - Sri Rahayu; Pangoloan Soleman Ritonga; Elvi Yenti (Journal of Chemistry Education and Integration, 2022)
It was a quasi-experimental research with pretest and posttest design.  It was instigated by the low of student learning achievement on Thermochemistry lesson.  This research aimed at knowing the effect of implementing Teams Games Tournament (TGT) learning model with Kokami media toward student learning achievement on Thermochemistry lesson.  The subjects of this research were the eleventh-grade students of Natural Science of State Senior High School 1 Tambusai Utara.  Simple random sampling technique was used in this research, and it was obtained two classes—the eleventh-grade students of Natural Science 2 as the experimental group and the students of Natural Science 1 as the control group.  The data were collected by using observation, preliminary data test that was homogeneity, final data tests that were pretest and posttest, and documentation.  Kp formula was used to know the effect of implementing TGT learning model with Kokami media toward student learning achievement.  The effect difference was analyzed by using independent sample t-test.  The analysis results of preliminary and final data showed that tobserved was 3.184 and ttable was 1.995 at 0.05 significant level.  The score of tobserved was higher than ttable, so H0 was rejected and Ha was accepted.  It meant that there was an effect of implementing TGT learning model with Kokami media toward student learning achievement on Thermochemistry lesson at the eleventh grade of Natural Science of State Senior High School 1 Tambusai Utara, and the effect was 16.3%.Keywords: Learning Achievement, Teams Games Tournament (TGT), Kokami Media, Thermochemistry